Legal Aspect and Legality in Corporate Companies - Ahmadun Ahmadun; Helena Louise Pangabean; Agnes Manuhutu; Andi Muhammad Sabilillah Tahir; Kamsariaty Kamsariaty (ABNUS Publisher, 2023)
The purpose of this article is to discuss the implementation of legal aspects and legality in the company, as well as its implementation in the company. In this article using Techniques that describe, by Analysis by collecting the necessary data from additional sources, and then analysis and clarified properly, scattering additional information, data for investigation is collected, Additional data is collected from books, research papers, articles, lecture notes, and the internet. Legal and legality aspects play an important role in the operation and management of corporate companies. Companies must ensure compliance with applicable laws and regulations in the jurisdictions in which they operate. This includes the process of forming and licensing a company, compliance in relationships with third parties, protection of confidential information and copyright, and adopting best practices in terms of legality. Corporate corporations need to have an in-house legal team or work closely with external law firms to provide legal advice, ensure regulatory compliance, and deal with legal issues that may arise. By maintaining compliance with legal and legal aspects, companies can reduce legal risks, maintain reputation, and create a healthy and sustainable business environment.